Sustainable Energy Through Wind Speed and Power Density Analysis in Ambam, South Region of Cameroon - Elie Bertrand, Kengne Signe; Abraham, Kanmogne; Lucien, Meva’a (Frontiers in Energy Research, 2020)
The characterization of the wind regime is one of fundamental importance, and the two parameters of Weibull distribution are the most applied function for it. In this present study, wind speed data of Ambam . Data obtained was analyzed to estimate wind power density. Wind speed was collected at height of 10 m. Results presented a good Weibull distribution to fit measured probability distribution and the best numerical used is empirical energy. For example, average value of wind power density based on root mean cube seed approaches were 93.7628 W/m2/year in 2013. This result presents Ambam as a marginal site for wind energy generation and the region possesses moderate wind characteristics. But it is very important to mention that, for a height of 10 m this potential is not negligible in Cameroon context where domestically energy (lighting, phone charge, radio and television,…etc)] is not yet available for the majority of villages, located far from the National electrical network.